Elders in modern Kenya: 'Dying institutions' or 'reinventing themselves'?. Issue 2 (3rd April 2018) - Nyamweru, Celia; Chidongo, Tsawe-Munga
ABSTRACT: The terms elders and Councils of Elders (CoE) do not appear in the Constitution of Kenya 2010 (CoK), and some scholars of African politics have suggested that these institutions are at odds with the ideals of modern democratic governance and will become increasingly less relevant in future decades. Other scholars stress their continued relevance at the local level, for example through providing affordable and easily accessible forms of alternative dispute resolution (ADR). We define the different categories of elders and CoE and use case studies from different parts of the country to illustrate their contributions to ADR and their relationship with government officials. We find that the 'local' elders and CoE have a continued and positive role that gets relatively little attention in the Kenyan media, in contrast to more prominent groups that seek influence in national politics, especially in the months preceding national elections. Despite their gerontocratic and patriarchal roots, these local groups show signs of evolving to include younger people and women in their membership; they address issues of real concern to the communities they serve. In recent years the Kenyan judiciary has begun to explore ways of encouraging the use of local CoE in ADR, and both national and county governments are recognising the need to provide more financial and logistical support to these bodies.